Analysis Of Critical Thinking Ability In Physics Of High School 17 Bone - Marwan, Aqil; Agustini*, Sri; Dahlan, Ahmad (Journal of Physics Education : Review and Research, 2025)
Critical thinking is an essential skill that students must develop, particularly in physics, which demands conceptual understanding and logical reasoning. This study aims to describe the level of critical thinking ability among Grade XI Science students at SMAN 17 Bone on the topic of static fluids through the implementation of the Problem-Based Learning (PBL) model. A quantitative descriptive method was employed, using essay tests based on five critical thinking indicators: providing simple explanations, building basic skills, drawing conclusions, providing further explanations, and developing strategies and tactics. The results showed that 81.48% of students were in the “Very Good” category, and 14.81% were in the “Good” category, with an average score of 24.70. The highest performance was in the “providing further explanation” indicator (70.06%), while the lowest was in “drawing conclusions” (57.41%). These findings indicate that the PBL model is effective in enhancing students' critical thinking skills, although improvements are needed in conclusion-making and strategic planning. The use of relevant contexts and real-world problem-solving approaches supported the success of the learning process.